Darbepoetin in chronic kidney disease and dialysis patients; an updated review of outcomes - Tarun Kumar Jeloka; Datta Jayanta; Suresh Babu Vallamkonda; Sujeet Narayan Charugulla; Gupta Namita (Society of Diabetic Nephropathy Prevention, 2020)
Individuals with chronic renal failure in stage three and after demonstrate anemia as a frequent complication. Although target hemoglobin levels remain debatable in pre-dialysis and dialysis patients, correction of anemia with erythropoiesis-stimulating agents (ESAs) has resulted in reduced need for blood transfusions, improved survival and enhanced overall quality of life. Owing to longer half-life and greater biological activity, darbepoetin alfa can maintain stable hemoglobin levels at extended dosing intervals. It is also economical and convenient with no compromise in efficacy. Studies have shown similar dose requirements for both intravenous versus subcutaneous darbepoetin in pre-dialysis and dialysis patients. This review article focuses on clinical outcomes of darbepoetin including the achieved hemoglobin target, maintenance of hemoglobin levels, all-cause mortality, cardiovascular events, additional blood transfusion, quality of life, and economic outcomes in patients with chronic kidney disease (CKD). This review also outlines the risk associated with darbepoetin administration and changes in guidelines recommendation for improving its use.